Does erectile dysfunction predict cardiovascular risk? A cross-sectional study of clinical characteristics in patients with erectile dysfunction combined with coronary heart disease - Li, Luyu; Zhang, Yongtao; Ma, Miaomiao; Liu, Feng; Shang, Yihan; Yuan, Quan; Li, Xiao; Ju, Baojun (Frontiers in Cardiovascular Medicine, 2024)
Background: Erectile Dysfunction (ED) is a common sexual dysfunction in men who are unable to consistently obtain and maintain sufficient penile erection to accomplish a satisfactory sexual life. ED is currently considered to be a predictor of cardiovascular disease (CVD), but there are few studies observing the association between ED and clinical features of Coronary heart disease (CHD). An investigation on the association between ED and clinical characteristics of CHD was carried out using a cross-sectional study design.This cross-sectional single center study was conducted in the Department of Cardiology and included 248 patients.Associations between patients' general information, underlying disease information, coronary heart disease information, and ED severity were statistically and analytically analyzed using SPSS 26.0 software. Patients with comparable clinical characteristics were grouped together using K-means clustering. Finally, ordered logistic regression analysis was performed for general and underlying disease information.In the comparison of general data, age, education and weekly exercise were associated with the distribution of ED severity; in the comparison of underlying disease information, the number of underlying diseases, hypertension, diabetes, hyperlipidemia, anxiety state, and depressive state were associated with the distribution of ED severity; in the comparison of CHD information, the degree of ED severity was associated with CHD subtypes, lesion sites, number of stenoses, degree of stenosis and interventional interventions; and the time from ED to CHD onset was associated with the subtypes of CHD and the number of stenoses. We clustered the main characteristics of low-risk and high-risk patients, and ordered logistic regression analysis found that BMI, smoking, alcoholism, number of underlying diseases, diabetes, anxiety state and depression state were all risk factors for CHD severity (P<0.05), and the presence of the above factors or the higher the value, the more severe the degree of CHD; age was a protective factor for CHD severity, when age is young, the likelihood of myocardial infarction is lower.ED severity and the time from ED to CHD onset may be predictive of coronary heart disease severity. Reducing smoking, alcohol consumption, maintaining a healthy body weight and regular physical activity are important in preventing CVD in ED patients.